Evaluation of a solar-driven adsorption desalination system for Brazilian semiarid region - Roberto Capparelli Marçal; Mário Benjamim Baptista de Siqueira (Applied Water Science)
Abstract In this study, the effect of using a hybrid solar thermal-activated adsorption desalination system for brackish water is evaluated under the climatic conditions of the Brazilian semiarid region. The proposed theoretical model utilizes climatic data from the meteorological station in Campina Grande, PB, and adsorptive kinetics data of Fuji Davison RD 260 silica gel to predict the performance indices of the specific daily water production (SDWP), specific cooling power (SCP), and coefficient of performance (COP) performance coefficients over a characteristic day. The SDWP value of 6.26 m3/ton, SCP ranging from 50 to 300 W/kg, and an average COP of 0.5 were obtained, considering variations in global horizontal irradiance in the ACDS system and transient ambient temperature. It was observed that both the production of desalinated water and the refrigeration effect increase with the rise in daily solar irradiance. The variation in the number of solar collectors used in the system and their optimality, as well as the variation in the salinity index of the feed source, impacted the evaluated performance coefficients.